Performance evolution of different controllers for frequency regulation of a hybrid energy power system employing chaotic crow search algorithm. (January 2022) - Guha, Dipayan; Roy, Provas Kumar; Banerjee, Subrata
Abstract: The work described herein compares the performance of different optimized controllers, viz. proportional–integral, proportional–integral–derivative (PID) with filter, two-degree-of-freedom (2DOF)-PID, 3DOF-PID, fractional-order-PID, cascade PI–PID, tilt-integral–derivative (TID), and cascade-TID (CC-TID) controllers in frequency regulation of a hybrid energy distributed power system (HEDPS). The HEDPS is integrated with a multi-unit hydrothermal power plant for ensuring stable power supply. Crow search algorithm has been adopted with chaotic mapping (CCSA) for fine-tuning of the controller settings mentioned above. Extensive analysis has been presented to confirm the superiority of the CC-TID controller compared to other prevalent controllers of state-of-art in terms of different performance specifications. The tuning competence of the CCSA has been demonstrated over conventional CSA and other available optimization techniques. To enhance the mastery of the controller, disturbance-observer (Dob) is developed to estimate fast-changing disturbance profiles and subsequently refines the control law. The controller's robustness is affirmed under random perturbations, presence of nonlinearities, and variation of parameters. The effect of integration of a geothermal power plant on the system performance has also been outlined. The efficacy of Dob-aided CC-TID controller in frequency regulation is validated thereof. Highlights: The performance of interconnected hybrid distributed power system has been assessed. The performance of various controllers in regulation of frequency has been observed and compared. Chaotic crow search algorithm is derived for optimization and competence has been confirmed with state-of-art optimization techniques. Robustness of the developed controller is confirmed under different perturbed scenario.